Fresno County Legal Services Holiday Party - Watkins, Howard K. (1976)
Front: Gloria Escalante, Janice Pearson, Alice Mendoza, Ruben Lucero, Darci Reid; Back: Ray Starks, Virginia Salmeron, Cristobal Perez, Robert Higgins